A new Amazonian species of Adenomera (Anura: Leptodactylidae) from the Brazilian state of Para: a tody-tyrant voice in a frog - De Carvalii, Thiago R. [UNESP]; Giaretta, Ariovaldo A.; Angulo, Ariadne; Haddad, Celio F. B. [UNESP]; Peloso, Pedro L. (Amer Museum Natural History, 2019)
Leptodactylid frogs are phenotypically diverse, widely distributed across the Neotropics, and are known to harbor high levels of cryptic species diversity. This is especially true in Adenomera, where several candidate species have been recognized in a genetics-based study. Here we describe a new Amazonian species of Adenomera, which corresponds to one of the lineages previously identified as a candidate species (sp. F). Adenomera phonotriccus, n. sp., differs from all 18 recognized congeners by its unique advertisement call. Moreover, this species can be distinguished from nearly all congeners (except A. cotuba and A. lutzi) in having antebrachial tubercles on the undersides of its forearms. The distribution of A. phonotriccus seems to be restricted to the Araguaia-Xingu interfluve, in the eastern portion of the Brazilian state of Para. Additional sampling effort on the right margin of the Araguaia River and along the Xingu River drainage should clarify the distribution of A. phonotriccus and perhaps result in the discovery of additional undescribed species of Adenomera in a region with high biological diversity.